Wayang Kulit Performance as Cultural Preservation and Its Influence on Visitors at the Old Town Wayang Museum - Ina Cahyani; Silvy Mei Pradita (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2024)
Abstract: This research aims to: (1) Analyze the cultural attractions of wayang kulit performances to attract the interest of visitors at the Kota Tua Wayang Museum. (2) Analyzing the role of shadow puppet performances as cultural preservation for visitors at the Kota Tua Wayang Museum. (3) Analyzing visitors' responses to the meaning conveyed in shadow puppet performances at the Kota Tua Wayang Museum. The results of this research show that the shadow puppet show at the Kota Tua Wayang Museum succeeded in attracting the interest of visitors through promotions on social media and the installation of banners, aimed at attracting people to visit the museum. This performance has a moral message and positive values by influencing visitors who feel an emotional closeness to the cultural preservation of this cultural attraction. This research uses qualitative research with a phenomenological approach. The conclusion of this research is that shadow puppet performances at the Kota Tua Wayang Museum have an important role in preserving shadow puppet culture. Abstrak: Penelitian ini bertujuan untuk: (1) Menganalisis atraksi budaya pada pagelaran wayang kulit untuk menarik minat pengunjung di Museum Wayang Kota Tua. (2) Menganalisis peran pagelaran wayang kulit sebagai pelestarian budaya bagi pengunjung di Museum Wayang Kota Tua. (3) Menganalisis respon pengunjung terhadap makna yang disampaikan pada pagelaran wayang kulit di Museum Wayang Kota Tua. Hasil dari penelitian ini bahwa pagelaran wayang kulit di Museum Wayang Kota Tua berhasil menarik minat pengunjung melalui promosi di media sosial dan pemasangan spanduk, ditujukan untuk masyarakat berkunjung ke museum. Pagelaran tersebut memiliki pesan moral dan nilai positif dengan mempengaruhi pengunjung yang merasakan kedekatan emosional untuk pelestarian budaya dari atraksi budaya ini. Penelitian ini menggunakan penelitian kualitatif pendekatan fenomenologi. Kesimpulan dari penelitian ini adalah pagelaran wayang kulit di Museum Wayang Kota Tua memiliki peran yang penting dalam pelestarian budaya wayang kulit.